Proteomics: Potential techniques for discovering the pathogenesis of connective tissue diseases-interstitial lung disease - Wu, Yinlan; Li, Yanhong; Luo, Yubin; Zhou, Yu; Liang, Xiuping; Cheng, Lu; Wu, Tong; Wen, Ji; Tan, Chunyu; Liu, Yi (Frontiers in Immunology, 2023)
Interstitial lung disease (ILD) is one of the most serious lung complications of connective tissue disease (CTD). The application of proteomics in the past decade has revealed that various proteins are involved in the pathogenesis of each subtype of CTD-ILD through different pathways, providing novel ideas to study pathological mechanisms and clinical biomarkers. On this basis, a multidimensional diagnosis or prediction model is established. This paper reviews the results of proteomic detection of different subtypes of CTD-ILD and discusses the role of some differentially expressed proteins in the development of pulmonary fibrosis and their potential clinical applications.